Pengaruh Pengetahuan Investasi dan Uang Saku terhadap Minat Berinvestasi pada Reksadana - Arini Indah Sridayani; Fitri Kumalasari; Agus Zul Bay (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine: (1) The Influence of Investment Knowledge on the Investment Intention of FISIP USN Kolaka students. (2) The Influence of Pocket Money on the Investment Interest of USN Kolaka students. This study used quantitative methods. Collecting data in this study used observation, literature study and distributing questionnaires. The population of this study were all FISIP USN Kolaka students class of 2019-2020 in the Management, Accounting and Development Economics study program. Determination of sample size used the slovin formula, amounting to 222 with the purposive sampling technique. Testing research instruments used validity and reliability tests with SPSS 22.0. The data analysis technique used in this study was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with measurement model testing (outer model), structural model testing (inner model) and second order with Smart PLS 4.0. Based on the results of the study that there was a significant influence between Investment Knowledge and Investment Intention, this indicated by a P-Value of 0.000. Likewise with Pocket Money there was an influence but not significant on Investment Intention, this indicated by the P-Value of 0.350.